Left Atrial Ganglionated Plexi Detection is Related to Heart Rate and Early Recurrence of Atrial Fibrillation after Surgical Ablation - Suwalski,Grzegorz (2017)
Abstract INTRODUCTION: Left atrial ganglionated plexi ablation is an adjuvant technique used to increase the success rate of surgical ablation of atrial fibrillation. Ganglionated plexi ablation requires previous detection. We aimed to assess determinants of successful ganglionated plexi detection and to correlate range of ganglionated plexi ablation with risk of early atrial fibrillation recurrence. METHODS: The study involved 34 consecutive patients referred for surgical coronary revascularization with concomitant atrial fibrillation ablation. Ganglionated plexi detection was done by inducing vagal reflexes in the area of the pulmonary veins and left atrial fat pads. RESULTS: Detection of GP was successful in 85% of the patients. There was no difference in preoperative characteristics nor in atrial fibrillation type between patients in whom ganglionated plexi detection was successful and others. The number of detected ganglionated plexi correlated significantly only with preoperative resting heart rate. Significant negative correlation was found in patients with preoperative heart rate>75 beat/min in terms of total number of detected ganglionated plexi (P=0.04). Average number of detected ganglionated plexi was significantly higher in patients with in-hospital atrial fibrillation recurrence requiring electrical cardioversion (3.8±3) in comparison to rest of the study population (2±1.3; P=0.02). In patients in whom 4 or more ganglionated plexi were detected, significantly increased risk of in-hospital atrial fibrillation recurrence was observed (OR 15; 95% CI 1.5-164; P=0.003). CONCLUSION: Left atrial ganglionated plexi detection was unsuccessful in a considerable percentage of patients. Preoperative heart rate significantly influenced positive ganglionated plexi detection and number of ablated ganglia. Higher number of detected ganglionated plexi was related with early recurrence of atrial fibrillation.